INOVASI KEGIATAN KEAGAMAAN DI HIJABERS COMMUNITY MALANG - Rohmah Istikomah; Umi Sumbulah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2023)
Hijab is now a new fashion trend among women. This stylish and modern hijab style phenomenon has attracted many Muslim women, especially the young ones. This fashionable hijab style was first introduced by a community known as the "hijabers community". This community plays an essential role in increasing the popularity of hijab in Indonesia because it changes the perception of Indonesian people towards the hijab which previously symbolized religious fundamentalism. Currently, hijab is seen positively as a symbol of modernity without having to abandon religiosity. Some hijabers communities established in Malang are the Hijabers Community Malang (HCM). The aims of this research is describing religious learning in HCM.The findings from this study encompasses the attainment of the religiosity concept instilled in the hijabers community, exploration of the meaning of education, savior, peace, refined sense of solidarity and transformative through religious activities taught in the hijabers community